Stage IV Colorectal Cancer at Initial Presentation versus Progression during and after Treatment, Differences in Management: Management Differences for Initial Presentation versus Progression of Disease after Initial Treatment - Monahan, Brian V.; Patel, Takshaka; Poggio, Juan Lucas (Clinics in Colon and Rectal Surgery, 2023)
Stage IV colorectal cancer is a prevalent disease and understanding the appropriate treatment options is important. Medical oncologic treatment remains the mainstay of treatment in cases where curative resection is not possible. Surgical intervention is indicated if the primary tumor and associated metastases are amenable to curative resection or if obstructive, bleeding, or perforative complications arise from the tumor. New endoscopic techniques can provide palliation and benefit for patients who cannot undergo surgery and may speed time to chemotherapy initiation. Recently, immunotherapy has shown promise at managing, controlling, and regressing advanced disease, in some cases converting it to curative with resection. For patients that progress while on treatment, continued medical therapy remains the mainstay of treatment. Further research into the benefits of asymptomatic primary tumor resection without curative intent needs to be performed. Colorectal cancer, and more specifically metastatic colorectal cancer, continues to have improved 1- and 5-year survival rates and likely will continue to do so over the coming months and years.
Keywords: metastatic colorectal cancer; stage IV colorectal cancer